Physical Properties of Soils from Several Land Uses in a Tidal Swampland Area Applied with a Fork Irrigation System - Susilawati, Ani; Nursyamsi, Dedi; Syahbuddin, Haris (JOURNAL OF TROPICAL SOILS, 2017)
In Indonesia, tidal swampland is potential to be developed into agricultural land uses. Water management is the key success of farming on the tidal swampland. In the tidal swampland of Kalimantan, Indonesia, a fork irrigation system is widely applied in the water channels to supply irrigation water to the land. Besides irrigation, soil physical characteristics play an important role in controlling water availability for crops. The ability of soil to store water will determine the amount of available water that can be taken up by plants. This research aimed to determine the soil physical properties that are related to water availability in the soils from different land uses in a tidal swamp land area applied with a fork irrigation system. The experiment was conducted in dry season 2012, in Belawang, Barito Kuala district, South Kalimantan province. The soil samples were taken from four land uses, namely rice field, rubber plantation, mixed cropping, and unmanaged land. The soil physical properties, namely soil bulk density, particle density, porosity, texture, pF 1, pF 2, pF 2.54, pF 4, water content, total pore space, rapid drainage pores, slow drainage pores, available water, groundwater level were measured. In addition, the mineralogical properties of the soils were measured as well. The results showed that the physical properties of the soils taken from different land use varied, however, the change of the land use did not cause changes in the soil mineralogical properties. The mineralogy of the soils from different land uses are relatively the same, namely: quartz, illite, and chlorite.Â